Assessment of 3D-Printed Bolus for Post-Mastectomy Breast Cancer Radiation Therapy: Urifa Nabihal Aini, Hayfa Annisa, Diska Maharani, Aditya Prayugo Hariyanto, Agus Rubiyanto, Nasori Nasori, Aloysious Mario, Endarko Endarko - Urifa Nabihal Aini Urifa Nabihal Aini; Hayfa Annisa Hayfa Annisa; Diska Maharani Diska Maharani; Aditya Prayugo Hariyanto Aditya Prayugo Hariyanto; Agus Rubiyanto Agus Rubiyanto; Nasori Nasori; Aloysious Mario Aloysious Mario; Endarko Endarko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
The fabricated 3D-printed bolus with 5 mm thick PLA and TPU materials was successfully used to analyze the air gap, relative electron density ( RED), and mass attenuation coefficient values for Post-Mastectomy Breast Cancer Radiation Therapy (PMRT). The 3D bolus was designed using 3D-Slicer Segment Editor software according to the thickness used, then smoothed and finished using Autodesk Meshmixer software, and printed on a 3D Creality printer. The air gap value was then analyzed by taking images from the phantom and 3D-printed bolus on a CT-Scan, then processed on Radiant DICOM, and the air gap value for the two 3D bolus materials was obtained. Analysis of two 3D bolus materials, PLA and TPU, showed that TPU is more suitable for bolus use in postmastectomy breast cancer cases based on its material properties. In addition, TPU is also better in terms of the air gap value because it has a smaller air gap, an RED value that is almost close to that of breast tissue, and better mass attenuation. Therefore, the recommended 3D-printed bolus material is TPU with a thickness of 5 mm as a tissue substitute for postmastectomy breast cancer cases.